From Stars to Life − Cold Organic Chemistry and Prebiotic Insights via Matrix Isolation – - Danho, Akkad; Justus Liebig University Giessen (My University, 2025)
Reactive intermediates are transient, highly reactive molecular species involved in chemical processes. It is proposed that such species might participate in the interstellar synthesis of complex molecules and in atmospheric processes. Enols and carbenes represent a class of reactive species capable of undergoing reactions under certain conditions to form prebiotic compounds. While these species have been detected in interstellar space, knowledge about their origin remains limited. Intermediates can be stabilized with the help of matrix isolation and other specialized techniques and characterized spectroscopically. Under cryogenic conditions, tunneling effects significantly impact the reactivity of molecules. In addition to the principles of thermodynamic and kinetic reaction control, tunneling control has emerged as a third fundamental paradigm of reactivity. In the first publication, prop-1-en-1,1-diol was isolated in a matrix for the first time and characterized using IR and UV/Vis spectroscopy. The enol was obtained via high-vacuum flash pyrolysis starting from methylmalonic acid. Under UV irradiation, the enol is converted into an isomer of propionic acid as well as to methylketene. Enol, ketene, and propionic acid have previously been detected in the interstellar medium, with the latter representing a fundamental prebiotic molecule. In a subsequent publication, 2-methylprop-1-en-1,1-diol was isolated in a matrix and identified by IR and UV/Vis spectroscopy. The enol was generated via high-vacuum flash pyrolysis of dimethylmalonic acid. In this process, dimethylketene formed as well. This enol demonstrates similar reactivity to the previously isolated prop-1-en-1,1-diol and tautomerizes to isobutyric acid under UV irradiation. Although 2-methylprop-1-en-1,1-diol has not yet been detected in space, isobutyric acid plays a significant role in biological processes. A third, yet unpublished study dealt with quantum mechanical tunneling control of alkyl carbenes. The aim was to influence the outcome of competing tunneling reactions through the appropriate selection of alkyl carbene isotopologs with protium and deuterium. In the course of the study, various alkyl carbenes were examined for their tunneling reactivity. Among these, the previously unknown alkyl carbene pentacyclo[5.4.0.0²,⁶.0³,¹⁰.0⁵,⁹]undecanylidene, was isolated and characterized. This carbene showed increased cryogenic stability compared to the known adamantylidene and only undergoes a [1,2]-H shift to homohypostrophene under irradiation. Only the study of protoadamantylidene, the isolation of which was unsuccessful due to its short half-life, revealed two competing tunneling reactions. Both the product of the [1,2]-H- shift and that of C–H insertion was observed. Based on these observations, hydrogen isotopes were selectively employed to control the tunneling reaction. This approach successfully influenced product formation, marking the first experimental evidence of an isotope-controlled tunneling reaction.
Keywords: ddc:540